2018
DOI: 10.4102/jtscm.v12i0.345
|View full text |Cite
|
Sign up to set email alerts
|

Capacitated vehicle routing problem model for carriers

Abstract: Background: The Capacitated Vehicle Routing Problem (CVRP) is one of the most important transportation problems in logistics and supply chain management. The standard CVRP considers a fleet of vehicles with homogeneous capacity that depart from a warehouse, collect products from (or deliver products to) a set of customer locations (points) and return to the same warehouse. However, the operation of carrier companies and third-party transportation providers may follow a different network flow for collection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…In their work, there was 15.7% improvement on opt − A − n33 − k5 instance. Rojas-Cuevas et al, [34] used Capacitated Vehicle Routing Problem for Carriers (CVRPfC) to solve distribution problem. The route planning were obtained through CVRPfC and the authors concluded that the CVRPfC can improve the competitiveness of the carriers by providing better fares to their customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their work, there was 15.7% improvement on opt − A − n33 − k5 instance. Rojas-Cuevas et al, [34] used Capacitated Vehicle Routing Problem for Carriers (CVRPfC) to solve distribution problem. The route planning were obtained through CVRPfC and the authors concluded that the CVRPfC can improve the competitiveness of the carriers by providing better fares to their customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Ref. [14], Rojas-Cuevas et al proposed a model named Capacitated Vehicle Routing Problem for Carriers to obtain optimal route planning. The distribution scenario they worked on deals with a fleet of vehicles depart from a vehicle storage depot, collect products from a set of customer points and deliver them to a specific warehouse before returning to the vehicle storage depot.…”
Section: Literature Surveymentioning
confidence: 99%
“…As geo-location data is mainly obtained from smart phones and other mobile devices used by people and organizations, using and sharing this data by developers of Geographic Information System (GIS) applications has been the subject of debate and discussion. This is due to concerns regarding the privacy and confidentiality of this data (Richardson, 2019;Blatt, 2012). Although security technology and government regulations are frequently developed and established to ensure the ethical use of geolocation data, publicly available databases are the main resource for academic and research purposes.…”
Section: Development Of Test Instancesmentioning
confidence: 99%